2005
DOI: 10.4012/dmj.24.14
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Used Commercial Phosphate-bonded Investments with Additional Mono-ammonium Phosphate

Abstract: Industrial waste is on the increase, resulting in severe environmental contamination. Against this background, this study sought to investigate the possibility of recycling used phosphate-bonded investments.Commercial phosphate-bonded investment was mixed and heated according to manufacturer's instructions, then powdered with a ball mill machine to be used as recycled investment (Code: R) . Mono-ammonium phosphate (NH4H2PO4) of 2, 5, 8, 11, and 14 g were added to 100 g of R because of residual MgO, and coded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In terms of casting method, a heat-shock casting method was also investigated to reduce the operation time 5) . Of late, our research focus is on the reuse of dental investments 4) . However, there are difficulties in reusing commercial products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of casting method, a heat-shock casting method was also investigated to reduce the operation time 5) . Of late, our research focus is on the reuse of dental investments 4) . However, there are difficulties in reusing commercial products.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are difficulties in reusing commercial products. In our previous research 4) , all investments tested had to be disposed of after each experiment. This is neither rare nor unusual in the field of dentistry, despite the public concern that industrial waste is causing severe environmental contamination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously investigated reuse of mold materials, and found that phosphate-bonded investments could be recycled 1) . We also developed a new type of dental casting investment consisting of only refractory materials without binder, which could also be reused 5) .…”
Section: Introductionmentioning
confidence: 99%
“…The quantity of industrial waste produced increases each year, and this has become a major environmental issue 1) . Reuse of casting metal is common [2][3][4] in dental laboratory works.…”
Section: Introductionmentioning
confidence: 99%